2020
DOI: 10.15587/1729-4061.2020.208634
|View full text |Cite
|
Sign up to set email alerts
|

Predicting deformations in the area of impact exerted by a bridge crossing based on the proposed mathematical model of a floodplain flow

Abstract: To develop the methods for predicting deformations on floodplain areas in the zone of influence of bridge crossings, a mathematical model of a suspended flow with grass vegetation was developed. The problem of calculating the hydrodynamic fields of velocities and pressure in artificially compressed flows refers to the theory of shallow water since the vertical size (flow depth) is substantially smaller than the horizontal dimensions, such as length and width. In accordance with this, the proposed model is base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In work [8], in order to determine the average depth of the flow under the bridge under the calculation conditions, the calculation of the total erosion is performed for the predicted cross-sections of the riverbed. The quasi-three-dimensional form of steady-state finite-difference flood flow equations proposed by the authors allows taking into account the law of distribution of the averaged hydrostatic pressure vertically and the distribution of suspended sediments, the influence of the cohesion of fine-grained soils and the resistance of vegetation on general and local erosion of the bottom, but it makes it difficult to determine the redistribution of water flows and sediments between river and floodplain sections of the river.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In work [8], in order to determine the average depth of the flow under the bridge under the calculation conditions, the calculation of the total erosion is performed for the predicted cross-sections of the riverbed. The quasi-three-dimensional form of steady-state finite-difference flood flow equations proposed by the authors allows taking into account the law of distribution of the averaged hydrostatic pressure vertically and the distribution of suspended sediments, the influence of the cohesion of fine-grained soils and the resistance of vegetation on general and local erosion of the bottom, but it makes it difficult to determine the redistribution of water flows and sediments between river and floodplain sections of the river.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Our review of the literature [1][2][3][4][5][6][7][8][9][10][11] revealed that in the cases of solving complex problems of studying riverbed processes for the practical purposes of designing bridges and other important hydraulic structures, it is necessary to use and improve numerical methods that make it possible to simulate hydromorphodynamic processes in riverbeds. Therefore, it is expedient to study the specific problem of river processes, namely the hydromorphodynamics of bottom and bank changes, through the integrated application of modern computer technologies with the use of GIS for the grid approximation of the calculation area and analysis of the calculation results.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The calculation of the total erosion under bridges is carried out for the projected cross-sections of a riverbed [7] in order to determine, under the estimated conditions, the average depth of a flow under the bridge. This is done by comparing the total erosion coefficient with the permissible one Р dop and the hydraulic characteristics of the flow (velocity V, depth H) on the verticals of the sub-bridge section.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…where L і is the length of the river section with the velocity of breakthrough wave movement V. For example, for a river with a well-formed riverbed, with narrow floodplains without large heads, at a slope of the bottom i=0.0012, the average velocity of movement along the riverbed and floodplain sections, according to [7], is V 1 =10 km/h. In this case, according to Table 1, this is a riverbed with a characteristic of 2 at a slope i=0.0015 and an average roughness n=0.140.…”
Section: Reservoir and Dammentioning
confidence: 99%